2012
DOI: 10.1007/s13304-012-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of hyaluronic acid, tea tree oil and methyl-sulfonyl-methane in a new gel medical device for treatment of haemorrhoids in a double-blind, placebo-controlled clinical trial

Abstract: Topical formulations are widely used in anti-haemorrhoidal treatment, but often lacking controlled clinical trials. Here, we report the results from a controlled clinical trial performed with a new gel medical device (Proctoial) containing hyaluronic acid with tea tree oil and methyl-sulfonyl-methane as major components. The total number of 36 haemorrhoidal patients (grade 1-3) was enrolled in a double-blind, placebo-controlled clinical trial and divided into 2 equal parallel groups. The anal pain, pain during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Three non-acne clinical studies also report reduced inflammation following application of tea tree oil products for treating haemorrhoids [54], ocular demodecosis [55] and tinea [56]. Of the tea tree oil acne studies, four showed that reductions in inflammatory lesion numbers were greater than reductions for non-inflammatory lesions [16,[19][20][21], whilst a fourth study showed little difference [18].…”
Section: Properties Of Tea Tree Oil Contributing To Clinical Efficacymentioning
confidence: 99%
“…Three non-acne clinical studies also report reduced inflammation following application of tea tree oil products for treating haemorrhoids [54], ocular demodecosis [55] and tinea [56]. Of the tea tree oil acne studies, four showed that reductions in inflammatory lesion numbers were greater than reductions for non-inflammatory lesions [16,[19][20][21], whilst a fourth study showed little difference [18].…”
Section: Properties Of Tea Tree Oil Contributing To Clinical Efficacymentioning
confidence: 99%
“…HS can mediate cell signaling by binding numerous extracellular ligands such as fibroblast growth factor and contributes to homeostasis of innate immunity . HA is highly viscous and forms a physical barrier on top of the gut epithelium . In dextran sodium sulfate induced colitis, HA expression is enhanced to support colonic epithelial repair .…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] HA is highly viscous and forms a physical barrier on top of the gut epithelium. [20,21] In dextran sodium sulfate induced colitis, HA expression is enhanced to support colonic epithelial repair. [22] Inflammatory bowel disease can be caused by modification of the glycosaminoglycan composition and distribution on gut epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…The significantly lower pain scores recorded at 1 week and the lower scores found at 2 weeks in the group receiving TendisulfurÒ enhanced rehabilitation, minimized complications, and increased compliance. The ingredients of this nutraceutical preparation have documented analgesic and trophic effects on tendons, muscles, ligaments, and cartilage [22,23,[39][40][41][42][43]. MSM is the first oxidized metabolite of dimethylsulfoxide (DMSO), which seems to have antiinflammatory and chemopreventive properties and to inhibit prostacyclin (PGI2) synthesis and free radical scavenging activity [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%